Deep vein thrombosis and pulmonary embolism in a patient with acute type B aortic dissection: a case report - Akgül, Engin; Alptekin Erkul, Gülen Sezer; Erkul, Sinan; Vural, Ahmet Hakan (The European Research Journal, 2019)
Acute dissection involving ascending aorta contains high risk of mortality and requires surgical treatment immediately. Venous thrombosis can manifested as deep vein thrombosis or pulmonary embolism. It may be isolated or complication of another disease. Because of pulmonary thromboembolism risk, treatment of deep vein thrombosis is strongly recommended. A 61-year-old male patient with severe back pain and shortness of breath presented to the emergency service. The findings of the physical examinations, chest x-ray and electrocardiogram were normal. Contrast-enhanced computerized tomography showed an aortic intimal tear that started just below the subclavian artery and extended into the iliac arteries. The patient was hospitalized and the medical treatment started. On the 4th day of clinical follow-up, pain and swelling started at his right leg with severe shortness of breath. Venous Doppler ultrasound was performed and there were thrombosis at popliteal, femoral and even at iliac veins. Computed tomography showed pulmonary embolism at pulmonary trunk. Aortic dissection treated with endovascular stent graft firstly to prevent aortic rupture because of anticoagulation and then pulmonary embolism treated with anticoagulant drugs. Hypercoagulation is a self defence of the body for limiting the aortic intimal tear to prevent aortic rupture. So many complications could be seen because of this situation and the physicians should be awaken for this.